The Rule of Thoughts - Book 2 - Dashner, James 1972- (New York : Delacorte Press, 2014)
"Michael and his friends, Sarah and Bryson, are still being chased by a cyber-terrorist. And now the government is after them, too"--
Keywords: Computer games -- Juvenile fiction; Virtual reality -- Juvenile fiction; Cyberterrorism -- Juvenile fiction; Terrorism -- Juvenile fiction; Science fiction; Computer games -- Fiction; Virtual reality -- Fiction; Cyberterrorism -- Fiction; Terrorism -- Fiction; Science fiction; JUVENILE FICTION / Social Issues / Emotions & Feelings